STUDENTS´ PERCEPTIONS ABOUT THEIR LEARNING PROCESS WITH THE USE OF LEARNING OBJECTS - Pacheco-Cortés, Adriana Margarita; Morales-Salas, Rubí Estela (PEOPLE: International Journal of Social Sciences, 2018)
Although many teachers and students are used learning objects (LO), however, we unknown the students´ perceptions of LO used, we need to know if they identify that this materials facilitates their learning. The general objective study was analyze students´ perceptions about their learning process with the use of LO in a group of master class by surveying. This research has been base on qualitative and quantitative research methods, for the data collection instrument used was a survey to evaluate and analyze the perceptions of students, each of the rating questions used a 4-point Likert-type scale, respondents were students from a master´s group, individual student responses the survey. At this moment, the data were used for evaluation of students´ perceptions. To accomplish this, the individual ratings were summed and averaged. Further statistical analysis to examine the student´s perceptions of significant perceptions about statement of research problem was also conduced. The results of the survey explored show that students who were part of the study group perceived a significant increase in their learning with the use of learning objects, and the student research skills too. It is observed that the students´ perception on the LO use, it was found that 40% of the participants indicated that they are agree that LO facilitated their learning, 30% affirmed that they are totally agree, 20% declared to disagree and 10% strongly disagree. The results of the survey revealed that most of the participants (70%) have a positive perception about the LO used.